Exploring The Student’s Problem-Solving Skills In Missouri Mathematic Project Learning From The Self-Regulated Learning In Statistics Material - Karim, Abdul; Ambarwati, Lukita; Aziz, Tian Abdul (Universitas Wiralodra, 2023)
Education is the heart of the world. Exploration activities demonstrate students' mathematical problem-solving skills. Research purposes; The first, Identification learning outcomes by describing high, medium, and low Self-Regulated Learning (SRL) problem-solving abilities through the Missouri Mathematics Project (MMP). The second is to find out if the MMP model has a role in achieving classical mastery in its ability to solve mathematical problems the average value is it purpose achieved ≥ 80 in 75% of all samples. Mixed method, concurrent embedded design. A total of 75 students of the 8th grade of the SMP Pesantren Attaqwa Bogor in 2022-2023. Data from Problem-solving skills tests, SRL questionnaires, and interviews. Include 6 subjects; two high SRL students, two medium SRL students, and two low SRL students are picked from the 75 SRL-enrolled students. The teacher of the topic to be questioned in this study choose which students to interview. The research results show that: First, Students with high SRL are able to master the 4 components of Polya problem solving; medium SRL students are still able to understand the problem, make a settlement plan, carry out the settlement plan but are less able to re-examine the work; low SRL students are able to understand the problem but are less able to make a settlement plan, carry out the completion plan and re-check the work. Secondly, the KPM of statistical material students in the MMP model exceeded the mastery learning average score of ≥ 80 in 75% of class VIII students.